Analyzing Virtual Reality Teaching Behaviors Based on Multimodal Data - Hu, Jianping (International Journal of Computer Science and Information Technology, 2024)
The paper begins with an introduction to the background and research objectives, as well as the scope and limitations of the study. It focuses on multimodal data in virtual reality teaching. It discusses the different types of multimodal data and how they can be collected and analyzed. It also explores the integration of multimodal data in virtual reality teaching that need to be taken into account.